2016
DOI: 10.1101/070227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eph/Ephrin Signaling Controls Progenitor Identities in the Ventral Spinal Cord

Abstract: 2 SUMMARY STATEMENTThis article by Laussu et al. describes a role for Eph:ephrin signaling in controlling the identity of neural progenitors in the ventral spinal cord. ABSTRACTEarly specification of progenitors of the ventral spinal cord involves the morphogen Sonic Hedgehog which induces distinct progenitor identities in a dose-dependent manner. Following these initial patterning events, progenitor identities have to be maintained in order to generate appropriate numbers of progeny. Here we provide evidence … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Mesengenesis of iPSCs by inhibiting TGF‐β/Activin/Nodal signaling with SB‐431542 resulted in a greater expression of VEGFR1 ( FLT1 ), a marker of vascular endothelial cells in iMSCs than in BM‐MSCs . Mesengenic induction using FGF2 and PDGF followed by cell sorting for a CD105 + CD24 − population also gave rise to a heterogeneous culture with greater expression of vascular endothelial markers ( CL‐P1 and FAM43A ) and neuroprogenitor markers ( EFNB3 , SLITRK5 , and CKAP2L ) in ESC‐MSCs than in BM‐MSCs . Moreover, irrespective of the derivation methods used, extremely low expression of MSC‐associated genes was often detected in these PSC‐MSCs, including IL6 , BST1 , SFRP4 , and VCAM1 .…”
Section: Discussionmentioning
confidence: 99%
“…Mesengenesis of iPSCs by inhibiting TGF‐β/Activin/Nodal signaling with SB‐431542 resulted in a greater expression of VEGFR1 ( FLT1 ), a marker of vascular endothelial cells in iMSCs than in BM‐MSCs . Mesengenic induction using FGF2 and PDGF followed by cell sorting for a CD105 + CD24 − population also gave rise to a heterogeneous culture with greater expression of vascular endothelial markers ( CL‐P1 and FAM43A ) and neuroprogenitor markers ( EFNB3 , SLITRK5 , and CKAP2L ) in ESC‐MSCs than in BM‐MSCs . Moreover, irrespective of the derivation methods used, extremely low expression of MSC‐associated genes was often detected in these PSC‐MSCs, including IL6 , BST1 , SFRP4 , and VCAM1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in animal models have demonstrated the role of EphrinB2 signalling in the lineage specification of motor neurons in the spinal cord (13) and dopaminergic neurons in the midbrain (15). Nevertheless, there are contradictory and conflicting data within the scientific literature regarding the role of EphrinB2 signalling in both the promotion and inhibition of the differentiation of neural stem cells and neural progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…The signalling pathways mediated by the family of EphB receptors and EphrinB ligands, which are expressed in the perivascular niche of the dental pulp, are known to serve key roles in the proliferation, mobilization and mineralization of DPSCs during the process of tooth regeneration, in response to injury of the dentin matrix (12). Of particular interest in the field of neuroregeneration are EphrinB2 and its cognate receptors EphB2 and EphB4, which have been demonstrated to serve key developmental roles in embryonic neurogenesis (13)(14)(15) as well as in the homeostasis and mobilization of neural stem cells (16) and neural progenitors (17). EphrinB2 and its cognate receptors EphB2 and EphB4 are transmembrane receptor tyrosine kinases, which are established to play crucial roles in cell migration and in the determination of cell lineage fate (18).…”
Section: Introductionmentioning
confidence: 99%
“…The ventral spinal cord is dependent on the morphogen Shh secreted from the floorplate and notochord, evidenced by failure of ventral spinal cord patterning in Shh −/− mice . Other factors may also have contributions to ventral patterning including Eph/Ephrin signaling, and Chordin , which is expressed in the notochord and inhibits Bmp signaling, but Hedgehog (Hh) signaling mediated by Shh has a dominant role. Pairs of cross‐repressive transcription factor genes lie downstream of the Shh signal.…”
Section: Patterning the Vertebrate Spinal Cord: The DV Axismentioning
confidence: 99%